A Phase 1 Trial to Evaluate the Relationship Between Fluoride Intake and Urinary Fluoride Excretion in Healthy Participants. (12th November 2021) - Gillespie, Gillian; Jackson Rudd, Deanne; Zhang, Saijuan; Schaeffer, Andrea; Tomek, Charles; Larson, Patrick; Stoch, S. Aubrey; Iwamoto, Marian
Abstract: Chronic overexposure to fluoride can have deleterious effects in the musculoskeletal system. Some fluorine‐containing therapeutics, such as voriconazole, release fluoride through metabolism. Therefore, drug‐related fluoride exposure should be assessed for novel therapeutics suspected of releasing fluoride through metabolism. Two trials were conducted to identify the optimal method of assessing drug‐related fluoride exposure. In trial 1, designed to assess reproducibility of fluoride pharmacokinetics in urine and plasma, 14 participants were administered a fluoride‐restricted diet and once‐daily doses of sodium fluoride (2.2 mg [1 mg of fluoride] on days 1 and 2; and 13.2 mg of sodium fluoride [6 mg of fluoride] on days 3 and 4). In trial 2, designed to confirm the selected method for fluoride detection, 12 participants were administered a fluoride‐restricted diet and randomized to receive voriconazole (400 mg twice, 12 hours apart, on day 1 [131 mg/d of fluoride maximum], then 3 doses of 200 mg every 12 hours [65.3 mg/d of fluoride maximum]) or placebo. Plasma fluoride concentrations and urinary fluoride excretion were assessed in each trial. Assessment of plasma fluoride concentrations in trial 1 was limited by 301 of 854 samples (35.2%) below the lower limit of quantitation. Urine fluoride excretion was readily measured and demonstrated a decrease from baseline during the fluoride‐restricted diet phase, as well as dose‐proportional increases with fluoride administration. In trial 2, increases in urine fluoride were successfully observed in participants administered voriconazole. In conclusion, fluoride exposure was optimally assessed by urinary fluoride excretion in conjunction with strict dietary fluoride restrictions, as measurements were consistent and reproducible.